The Diagnostic and Therapeutic Challenges of A Progressive Male Breast Cancer with Brain Metastases: A Case Report - Putra, Benaya; Hamdani, Fakhriel Muhammad; Afnan, Alvin (Indonesian Journal of Medicine, 2026)
Background: Male breast cancer (MBC) is a rare malignancy that is often associated with advanced stages and poor prognosis due to lack of public awareness and early screening, along with stigmatization of the disease. Aims: This case report aims to highlight the diagnostic and therapeutic challenges of rapidly-progressive MBC in resource-limited healthcare, particularly those compounded by systemic and patient-attributable delays, and emphasize the importance of prevention and early detection of breast cancer in the male population. Subject report: We report the case of a 71-year-old man with a three-month history of a progressively enlarging lump on right breast, weight loss, and right-sided hemiparesis. Medical history included chronic heart failure, dyslipidemia, heavy smoking, and labour work background. The diagnosis of invasive ductal breast carcinoma was established through clinical assessment, imaging, and biopsy. Results: The patient underwent primary tumor resection (PTR) in the form of radical mastectomy, where the main purpose was tumor debulking, revealing tumor invasion into the pectoralis major muscle (pT4 disease). The clinical course was severely impacted by Treatment Delay, encompassing Provider Delay and Patient Delay, which was caused by logistical, operational, and policy barriers. This delay critically postponed the scheduled non-contrast computed tomography (CT) of the head. The delayed CT subsequently revealed multiple metastases. The patient was then referred for immunohistochemistry (IHC) evaluation and systemic therapies but passed away before the scheduled workup due to a declining neurological state from confirmed brain metastases. Conclusion: This case underscores how the challenges of rapidly progressive MBC with brain metastases, combined with a variety of delays and constrained treatment options, resulted in a poor outcome. It highlights the critical need for increased awareness, stigma reduction, and streamlined resource pathways to improve early detection and timely intervention in resource-limited settings.